IN HOUSE TRAINING OPTIMIZATION FACTORS EKSPOSI HSG EXAMINATION FOR PATIENT SUPPORT AND RADIATION SAFETY IN RS ROEMANI - Siti Masrochah; RIni Indrati; Sri Mulyati (Jurnal LINK, 2016)
Along with the development of technology various radiographic increasingly varied from a single exposure to the examination in serial. Including reproductive organs, one of which is known as Histerosalfingography examination (HSG) (Bontrager, 2000). Histerosalfingography is done by making a couple of times to get the radiation exposure according to the radiograph contrast media travel in the reproductive system. Therefore, patients also gain some exposure (exposure) radiation projection includes at least Antero posterior (AP), oblique, and lateral. On the other hand, the reproductive organs is one of the organs that are sensitive to radiation (Travis, 2000), it makes reality a dilemma, on one hand radiographs are required to get information anatomical features optimized to support diagnostic, on the other hand the sensitivity of organs high against radiation. Therefore, it is necessary election eksposi factors and appropriate treatment so that the negative effects of radiation does not occur in patients who do checks. It is necessary for the dissemination of research on the radiation dose received at each examination of the reproductive system (HSG) is. Thus, the method can be applied optimization Exposure factors in Histerosalfingography Examination for patient safety (patient safety) that need to be upheld in all health services.